When Coal Was King: Ladysmith and the Coal-Mining Industry on Vancouver Island - Mouat, Jeremy (Labour / Le Travail, 2005)
The article reviews the book, "When Coal Was King: Ladysmith and the Coal-Mining Industry on Vancouver Island," by John R. Hinde.